A Comparative Study of Endoscopic Versus Otomicroscopic Myringoplasty - Tulachan, Bishow; Acharya, Roshan; Borgohain, Buddha Nath (Journal of Universal College of Medical Sciences, 2018)
Introduction: Myringoplasty is one of the common surgical procedures done for closure of perforated tympanic membrane. Traditionally, it used to be performed with the help of operating microscope, however, the rigid endoscopes are being popular nowadays. So, we are comparing the success of graft uptake between endoscopic versus otomicroscopic myringoplasty. Materials and methods: This is a prospective, comparative and randomized study done in the Department of Otorhinolaryngology and Head and Neck Surgery (ORL-HNS), Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), Bhairahawa, Nepal. The study duration was for 18 months (1st December 2015 to 31st May 2017). There were 60 patients with age range of 12-60 years. All the patients fulfilling the inclusion criteria were included. Patients were randomized into Group A (endoscopic) and Group B (otomicroscopic). Results: Patient's age ranged from 12-60 years. The mean ± standard deviation (S.D) of age (years) between two groups was 27.07 ± 11.96 years and 27.20 ± 9.65 years respectively. There were 33.33% male and 66.67% female patients in group A and 43.33% male and 56.67% female patients in group B. The graft uptake success rate was 93.33% in group A and 90% in group B. Statistically no significant difference was observed in graft success and failure rates between two groups (p =0.640). Conclusion: Comparatively the rate of graft uptake was higher in endoscopic group without statistical significance. Thus, endoscopic myringoplasty can be a good alternative of microscopic myringoplasty.